Implementasi Peraturan Bupati Tapin Nomor 22 Tahun 2018 Tentang Kebijakan Dan Strategi Daerah Dalam Pengelolaan Sampah Rumah Tangga Dan Sampah Sejenis Sampah Rumah Tangga Di Kabupaten Tapin (Studi Kasus Di Kelurahan Bitahan) - Arlan, Agus Sya’bani (LPPM STIA Banten, 2024)
The problem phenomenon that occurs is that the Bilahan sub-district does not have the facilities and infrastructure to manage household waste and household-like waste, there is a lack of socialization from the sub-district and district governments to the community, and there is a lack of public awareness regarding the cleanliness of the community environment. In Article 8 paragraph 2, the Regent is responsible for procuring land, facilities and infrastructure for managing household waste and similar types of household waste in accordance with the provisions of statutory regulations. This research aims to find out how implementation is, the factors that influence implementation and what efforts are made to overcome inhibiting factors in implementation. This research uses a qualitative descriptive research method. Data collection techniques are observation, interviews and documentation. The data source was taken through a sampling technique, namely purposive sampling, totaling 12 people. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. And using data credibility tests is carried out, among other things, by extending observations, increasing persistence in research, triangulation, negative case analysis, using reference materials and holding member checks. The results of the research show that the implementation of Tapin Regent Regulation Number 22 of 2018 concerning Regional Policies and Strategies in the Management of Household Waste and Waste Similar to Household Waste in Lokpaikat District, Tapin Regency (Case Study of Bilahan Subdistrict) is not yet good, there are 6 sub-variables and 14 indicators, 10 indicators are not yet good and 4 indicators are quite good. The indicators that are quite good are goals, coordination, economic conditions and social conditions. Meanwhile, indicators that are not good are measures of success, human resources, budget resources, implementer time resources, formal organization, informal organization, implementor response, problem cognition, cooperation, and political conditions. The driving factors are goals and coordination. Inhibiting factors are the absence of waste management facilities, lack of socialization and lack of public awareness. The researcher's suggestion to the Head of the Land and Environment Service is to carry out regular outreach through the sub-districts and sub-districts/villages, the head of the Bitahan Village, Lokpaikat District, Tapin Regency so that they can allocate the budget for waste management facilities and the community is expected to have awareness and cooperation regarding waste management.